Significant acceleration of nitriding kinetics in pure iron by pressurized gas treatment. (15th November 2015) - Wang, Bo; Fu, Wantang; Dong, Fan; Jin, Guofeng; Feng, Weiwei; Wang, Zhenhua; Sun, Shuhua
Abstract: The effect of nitriding pressure on the formation of nitrides and the nitriding kinetics in pure iron were investigated by applying pressurized gas nitriding at 500 °C for 5 h. Increasing the nitriding pressure from 1 atm (conventional nitriding condition) to 5 atm significantly increased the nitrided layer thickness from about 210 μm to 1100 μm. Furthermore, it was found that the constituents of the compound layer can be controlled by changing the nitriding pressure. These improvements are related to the fast reaction rates and high inward diffusive flux of nitrogen during the pressurized gas nitriding. Graphical abstract: Highlights: The pressurized gas nitriding behavior of pure iron was investigated. The effect of nitriding pressure on the formation of nitrides was discussed. Nitriding kinetics can be significantly accelerated by pressurized gas treatment. The composition of the compound layer can be controlled by nitriding pressure.